Isolation of a novel bio-peptide from walnut residual protein inducing apoptosis and autophagy on cancer cells. Issue 1 (December 2015) - Ma, Sihui; Huang, Di; Zhai, Mengxin; Yang, Lubing; Peng, Sen; Chen, Changxu; Feng, Xiaoru; Weng, Qiang; Zhang, Bolin; Xu, Meiyu
Abstract Background Walnut is unique because they have a perfect balance of n-6 and n-3 polyunsaturated fatty acids. The increasing market demand of walnut lipids results in the large amount of the oil extraction residue. The walnut residue is rich in nutritional proteins, and the uneconomic use of the by-product discouraged the development of walnut industry. Anticancer peptides have recently received attention as alternative chemotherapeutic agents that overcome the limits of current drugs. The aim of this study was to investigate whether anticancer bioactive peptide is contained in walnut. Methods Walnut residual protein was hydrolyzed separately by five different proteases. The sequential purification of the hydrolysates was carried out by ultra-filtration, gel filtration chromatography and RP-HPLC to obtain a cancer cell growth inhibitory peptide. Cell cycle distribution, Annexin V-FITC/PI double staining, TUNEL assay, western blot and immunofluorescence for LC3-II assay were used to detect apoptosis and autophagy on cells. Cytokine production was measured by ELISA kits, macrophage phagocytosis was measured by neutral red uptake assay, nitric oxide production was measured by Griess reagent. Results The hydrolysates of walnut residual protein produced by papain under the optimal conditions (5 % substrate concentration and an enzyme-substrate ratio of 10 % at temperature 60 C for 3 h), showed significant growth inhibitory activity on MCF-7. The amino acid sequence of the purified peptide was identified as CTLEW with a molecular weight of 651.2795 Da. It is a novel bio-peptide with an amphiphilic structure. CTLEW induced both apoptosis and autophagy on MCF-7 cells, inhibited the cancer cells growth of Caco-2 and HeLa significantly, but did not show any cytotoxic activity against non-cancerous IEC-6 cells. Moreover, the bio-peptide enhanced proliferation and IL-2 secretion of spleen lymphocytes, promoted phagocytosis and NO production of macrophages. Conclusion These results suggested that a novel bio-peptide, CTLEW inducing apoptosis and autophagy on MCF-7 cells can be released from walnut residual protein through papain hydrolyzing under the certain condition. The bio-peptide shows selective inhibition towards cancer cells growth and immunomodulatory activity.